(3OjhGf GdHcQj GdUOjbjs - (3GdHcQj , eMeO Hf eMeO CHj GdMSf Hf eMeO Hf YHO GdQMef, TeS GdOjf CHh GdecGQe,J (B994 (3g` s
(3ChdgG (B:s
(3hHYO(B: (3aeG ef eYfi Naj hOb, EdG hdg aj GdbhGHd eYfi QGb hQqb hgPG WQQ dNdY GdMbGFb ef WQa GdcdeGJ GdQbGFb s
(3BNQgG (B:s
(3bGd dj CSeY CLH bdJ dHjc QHjg gPG eG LGOJ Hg ehGWf GdCbdGe ef YhGQa gPG GdYGQa HCSQGQ GdeYGQa s
(3GfXQ GdLRA GdChd HQbe (B290 (3COH OjhGf GdHcQjs
(3hQO CjVkG JMJ Qbe (B2092s
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B7 - (3U (B60 ; (3eYLe GdeDdajf ; YeQ QVG cMGdI (B, (3J (B1408 (3g` (B/ 1987 (3e(B: (3L (B11 - (3U (B281s
(3agQS GdeNWhWGJ GdeUhQI (B((3eYgO GdeNWhWGJ GdYQHjI(B) - (3LRA (B1 - (3bSe (B3 - (3U (B44 ; (3cTa GdXfhf dMGLi NdjaI(B: (3L (B1 - (3U (B493s
(3eUOQ GbJfGA GdCUd (B:s
Keywords: (3GdCOHs